Pengaruh Efikasi Diri Dan Lingkungan Keluarga Terhadap Minat Berwirausaha Siswa - Yulia Evaliana (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2015)
This study aims to description of self-efficacy, family environment, and interest in entrepreneurship, and to determine the partial effect of self-efficacy and family environment on the entrepreneurship interest, and to determine the dominant effect between the variables of self efficacy and family environment on the entrepreneurship interest. The population in this study is eleventh grade student that consist of 445 students, a sample of 156 students with used proportionate random sampling technique. The method used is descriptive analysis and multiple linear regression. In this study indicates that self-efficacy, family environment, and entrepreneurship interest student’s variable is relatively good, self efficacy and family environment variable show that there is a partial effect on student’s interest on entrepreneurship, and self efficacy is the dominant variable affecting the interest in entrepreneurship students.ABSTRAK: Penelitian ini bertujuan untuk mendeskripsikan efikasi diri, lingkungan keluarga, minat berwirausaha, dan mengetahui pengaruh efikasi diri dan lingkungan keluarga secara parsial terhadap minat berwirausaha, serta untuk mengetahui pengaruh dominan yang mempengaruhi minat berwirausaha siswa. Populasi penelitian ini siswa kelas XI dengan jumlah 445 siswa, sampel sebesar 156 siswa dengan menggunakan teknik proportionate random sampling. Metode yang digunakan adalah analisis deskriptif dan regresi linear berganda. Hasil penelitian menunjukkan bahwa efikasi diri, lingkungan keluarga, minat berwirausaha siswa tergolong baik, efikasi diri dan lingkungan keluarga secara parsial mempengaruhi minat berwirausaha siswa, serta efikasi diri adalah variabel dominan yang mempengaruhi minat berwirausaha siswa.